A Comprehensive Review on Effects of Peritoneal Dialysis in the Treatment of Acute Renal Damage - Sanjana Bhagat; Shubham Tiwari (Indian Journal of Medical Biochemistry)
Aim and objective: To evaluate the prevalence and impact of physical symptoms in peritoneal dialysis (PD) patients, assess the effectiveness of PD in managing acute kidney injury (AKI) during COVID-19 and in patients who are suffering from congestive heart failure (CHF), investigate the incidence of vascular calcification and the role of biocompatible PD solutions (BPDSs) in improving patient outcomes. Background: When treating acute renal failure, PD involves inserting a catheter into the abdomen, and a special fluid is introduced to draw waste and excess fluids from the blood through the peritoneal membrane. This process helps to balance electrolytes and remove toxins from the body. Compared to hemodialysis, PD offers advantages such as flexibility in scheduling, fewer dietary restrictions, and preservation of residual kidney function. However, potential complications include infection, hernias, and fluid overload. Overall, PD can be an effective option for managing acute renal failure, but careful monitoring and management of complications are essential. Conclusion: Peritoneal dialysis is a practical and safe alternative to hemodialysis for patients without established access. It offers acceptable complication rates and patient and method survival. Comprehensive renal replacement therapy (RRT) programs should include a tailored educational program for a successful PD urgent start.